Associations of Dietary Inflammatory Index With Prediabetes and Insulin Resistance - Shu, Yanling; Wu, Xiaocong; Wang, Jiating; Ma, Xiang; Li, Huawen; Xiang, Yun (Frontiers in Endocrinology, 2022)
Background and aims: Previous studies suggested that dietary inflammatory index (DII) was associated with a variety of adverse health conditions. However, less is known about the role of DII in prediabetes and insulin resistance (IR). Therefore, this study aimed to investigate whether DII is associated with prediabetes and IR in American adults. Method and Results: DII scores were calculated using the average of two 24-hour dietary recalls. Linear regression models were performed to evaluate the associations of DII with markers of Type 2 diabetes (T2D) risk, and the associations of DII with prediabetes and IR were estimated using logistic regression model. The diet of the participants showed an anti-inflammatory potential, with a mean DII score of -0.14 (range: -5.83 to +5.32). After controlling for multiple potential confounders, DII scores were positively associated with fasting plasma glucose (FPG) (β: 0.009; 95% CI: 0.005 to 0.012), fasting serum insulin (FSI) (β: 0.083; 95% CI: 0.067 to 0.099) and homeostatic model assessment of insulin resistance (HOMA-IR) (β: 0.092; 95% CI: 0.075 to 0.109). Participants in the highest tertile of DII score have increased odds of prediabetes (OR: 1.40; 95% CI: 1.17 to 1.69; P for trend <0.001) and IR (OR: 1.79; 95% CI: 1.49 to 2.14; P for trend <0.001) compared with those in the first tertile of DII score. Conclusions: This study indicates that DII was positively associated with FPG, FSI and HOMA-IR, and a more pro-inflammatory diet was related to increased odds of insulin resistant and prediabetes.